Glucose-6-Phosphate Dehydrogenase Deficiency and Adrenal Hemorrhage in a Filipino Neonate with Hyperbilirubinemia - Akira Ohishi; Daizo Ueno; Tsutomu Ogata (Thieme Medical Publishers, Inc., 2013)
Abstract We report on a Filipino neonate with early onset and prolonged hyperbilirubinemia who was delivered by a vacuum extraction due to a prolonged labor. Subsequent studies revealed adrenal hemorrhage and glucose-6-phosphate dehydrogenase (G6PD) deficiency. It is likely that asphyxia and resultant hypoxia underlie the occurrence of adrenal hemorrhage and the clinical manifestation of G6PD deficiency and that the presence of the two events explains the early onset and prolonged hyperbilirubinemia of this neonate. Our results represent the importance of examining possible underlying factors for the development of severe, early onset, or prolonged hyperbilirubinemia.